Collaborative Outcome Mapping - Dart, J.; Roberts, M. (2014)
Collaborative Outcomes Reporting (COR) is a participatory approach to impact evaluation based around a performance story that presents evide nce of how a program has contributed to outcomes and impacts, that is then reviewed by both technical experts and program stakeholders, whic h may include community members. Collaborative Outcomes Reporting (COR ) is a participatory approach to impact evaluation based around a perf ormance story that presents evidence of how a program has contributed to outcomes and impacts, that is then reviewed by both technical exper ts and program stakeholders, which may include community members. Deve loped by Jess Dart, COR combines contribution analysis andMultiple Lin es and Levels of Evidence (MLLE), mapping existing data and additional data against the program logic to produce a performance story. Perfor mance story reports are essentially a short report about how a program contributed to outcomes. Although they may vary in content and format , most are short, mention program context and aims, relate to a plausi ble results chain, and are backed by empirical evidence (Dart and Mayn e, 2005). The aim is to tell the ‘story’ of a program’s performance us ing multiple-lines of evidence. COR adds processes of review by an exp ert panel and stakeholders, sometimes including community members, to check for the credibility of the evidence about what impacts have occu rred and the extent to which these can be credibly attributed to the i ntervention. It is these components of expert panel review (outcomes p anel) and a collaborative approach to developing outcomes (through sum mit workshops) that differentiate COR from other approaches to outcome and impact evaluation.